IFN-α Is Constitutively Expressed in the Human Thymus, but Not in Peripheral Lymphoid Organs - Colantonio, Arnaud D. (Public Library of Science, 2011)
Type I interferons have been typically studied for their effects in the context of bacterial or viral infections. However in this report, we provide evidence that Interferon-alpha (IFN-α) expressing cells are present in the thymus in the absence of infection. We show that pDC express the highest level of IFN-α and that MxA, which is exclusively expressed after engagement of the type I IFN receptor by IFN-α/β, is expressed in normal fetal and post-natal thymus, but not in the periphery. The highest level of MxA is expressed in mature thymocytes and pDC located in the medulla and at the cortico-medullary junction. The anti-microbial peptide LL-37, which is expressed in the thymus, when complexed with eukaryotic nucleic acids, induces the secretion of IFN-α by thymic pDC. This results in the upregulation of MxA expression in responsive thymocytes. We propose that the secretion of IFN-α in the thymus may function to regulate the rate of T cell development and modulate the requirements for the selection of developing T cells.